PUBLIC COMMUNICATION PROBLEMS VS HOAX "IN THE CONTESTATION OF ISLAMIC POLITICAL IN INDONESIA" - Yoga Budi Pratama Irawan; Mailin Mailin (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
ABSTRACTThe pattern of political communication in this multimedia era has relied heavily on the presence of new internet-based media, such as Facebook, Twitter, Instagram, YouTube, Line Today, etc. Mastery of information technology is part of the emergence of the power of new media, which of course brings a change in society. Anyone, including the new media users, can now also be directly involved in the process. This change in society is what the writer wants to write about because its impact on the pattern of political communication is felt. The interaction between voters and the elected is no longer hampered by distance and time, so the quality of political communication in democracy should be able to improve, this often happens because hoax news is a pleasure for those who read and enjoy any information that is not true. Political communication can run in two directions or even more so that feedback from the public can be directly received. On this basis, the new media has an important significance about current political communication activities. The author conducted a descriptive qualitative analysis by collecting secondary data and information through a literature review. The results of the author's research show that the presence of new media has a significant impact on political activity, especially the process of political communication. The author recommends that political communication activities should be carried out more thorough cyber media, to have a wider impact. Keywords: Public Communication, Hoax, Islamic Politics